2016
DOI: 10.3389/fnagi.2016.00259
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Nodal and Hub Organization Account for Brain Network Abnormalities in Parkinson’s Disease

Abstract: The recent application of graph theory to brain networks promises to shed light on complex diseases such as Parkinson’s disease (PD). This study aimed to investigate functional changes in sensorimotor and cognitive networks in Parkinsonian patients, with a focus on inter- and intra-connectivity organization in the disease-associated nodal and hub regions using the graph theoretical analyses. Resting-state functional MRI data of a total of 65 participants, including 23 healthy controls (HCs) and 42 patients, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 64 publications
6
38
0
Order By: Relevance
“…For example, dysfunction of somatomotor networks is not surprising, given the characteristic motor manifestations of PD (Jankovic 2008) and previous reports of their disruptions (Hacker et al 2012;Gottlich et al 2013;Olde Dubbelink et al 2014;Campbell et al 2015;Canu et al 2015;Gorges et al 2015;Tan et al 2015;Guimaraes et al 2016;Koshimori et al 2016;Peraza et al 2017). However, we show disruptions of internetwork somatomotor interactions.…”
Section: Pd Impacts Specific Cortical and Subcortical Network And Esupporting
confidence: 66%
“…For example, dysfunction of somatomotor networks is not surprising, given the characteristic motor manifestations of PD (Jankovic 2008) and previous reports of their disruptions (Hacker et al 2012;Gottlich et al 2013;Olde Dubbelink et al 2014;Campbell et al 2015;Canu et al 2015;Gorges et al 2015;Tan et al 2015;Guimaraes et al 2016;Koshimori et al 2016;Peraza et al 2017). However, we show disruptions of internetwork somatomotor interactions.…”
Section: Pd Impacts Specific Cortical and Subcortical Network And Esupporting
confidence: 66%
“…Further investigations have aimed to explore functional changes in sensorimotor and cognitive networks in PD, focusing on inter‐ and intraconnectivity organization in the disease‐associated nodal and hub regions, using graph theoretical analyses. To date, findings have highlighted diffuse alterations in nodal organization and regional hub disruption that result in a number of distributed abnormalities across brain networks that may be related to the specific clinical manifestations of PD …”
Section: Mri In Pdmentioning
confidence: 99%
“…To date, findings have highlighted diffuse alterations in nodal organization and regional hub disruption that result in a number of distributed abnormalities across brain networks that may be related to the specific clinical manifestations of PD. 126 The Role of Ultra-High Field Imaging Despite several limitations, MRI has certainly enhanced the diagnostic accuracy in the differential diagnosis of neurodegenerative parkinsonism over the last years.…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the characteristics of the brain networks can be investigated with graph-theory, which divides the networks in nodes (the brain regions) and in edges , representing the connections between the nodes ( Bullmore and Sporns, 2009 , Van Den Heuvel et al, 2010 ). Most graph-theoretical studies in PD showed significant reductions in both global and local parameters compared with HC ( Göttlich et al, 2013 , Koshimori et al, 2016 , Luo et al, 2015 , Skidmore et al, 2011 , Tinaz et al, 2016 ) but increased graph parameters have also been found in PD compared with HC ( Göttlich et al, 2013 , Zhang et al, 2015 ). A graph theory approach may contribute to understanding of cognitive impairment in PD.…”
Section: Introductionmentioning
confidence: 99%